DECOMPOSITION RATE OF LITTERFALL MANGROVE Rhizophora sp. AT SUNGAI BERSEJARAH MANGROVE AREA, KAYU ARA PERMAI VILLAGE, SUNGAI APIT DISTRICT, SIAK REGENCY, RIAU PROVINCE - Hersa, Tania; Efriyeldi, Efriyeldi; Amin, Bintal (Asian Journal of Aquatic Sciences, 2022)
This research was carried out in February 2021 in the Historic River Mangrove Tourism Area, Kayu Ara Permai Village, Sungai Apit District, Siak Regency, Riau Province. This study aims to analyze the rate of decomposition of inter mangrove litter. The method used in this study is a survey method and the determination of the sampling location by purposive sampling. The rate of decomposition of mangrove leaf litter was carried out by placing 10 g of litter in a litter bag on the mangrove forest floor in three zones for 4 weeks and taken every week as a sample. The results showed that the water quality, namely the temperature ranged from 28-30°C, salinity 30-31‰, and pH 6.1-6.4. The results of the calculation of the rate of decomposition of mangrove leaves obtained an average of 0.25–0.11 g/day. The results of the Anova test showed that the rate of decomposition of mangrove leaf litter was higher in zone 1, which is relatively always inundated by tides and is affected by sea waves.